2021
DOI: 10.5194/aab-64-223-2021
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effects of <i>BMPR1B</i>, <i>BMP15</i>, and <i>GDF9</i> genes on litter size in Ramlıç and Dağlıç sheep

Abstract: Abstract. This study was carried out to determine the presence of polymorphisms in genes affecting litter size. The SNPs in bone morphogenetic protein receptor type 1B (BMPR1B), bone morphogenetic protein 15 (BMP15), and growth differentiation factor 9 (GDF9) genes were detected in 60 uniparous and 60 multiparous ewes from Ramlıç and Dağlıç breeds. The ewes are maintained in nine public herds at the breeding station of the Afyonkarahisar Sheep and Goats Breeders' Association and lambed in two consecutive breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Texel is one of the most known muscled sheep breeds. The single nucleotide polymorphism (g+6723G > A) found in the 3 UTR region of GDF8 gene in Texel sheep which is known as myostatin was reported to cause superior muscularity (Clop et al, 2006;Çelikeloglu et al, 2021;Grasset et al, 2009;Johnson et al, 2005;Yalçın et al, 1978;Yayvan and Özkul, 2018). This mutation accelerates growth and increases muscularity in Texel and does not have a negative effect on the eating quality and intramuscular fat of the loin (Kijas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Texel is one of the most known muscled sheep breeds. The single nucleotide polymorphism (g+6723G > A) found in the 3 UTR region of GDF8 gene in Texel sheep which is known as myostatin was reported to cause superior muscularity (Clop et al, 2006;Çelikeloglu et al, 2021;Grasset et al, 2009;Johnson et al, 2005;Yalçın et al, 1978;Yayvan and Özkul, 2018). This mutation accelerates growth and increases muscularity in Texel and does not have a negative effect on the eating quality and intramuscular fat of the loin (Kijas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a candidate gene, BMP15 were well documented in the world for sheep fecundity. In general, the interest in fecundity gene research has been more on sheep in Türkiye, as is the case all over the world (Hanrahan et al, 2004;Wang et al, 2015;Çelikeloğlu et al, 2021;Kırıkçı, 2023a;Kırıkçı, 2023b). The main reason for this may be the consumption of more sheep meat within small ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many studies have shown that BMPR1B is associated with litter size in animals [32][33][34]. It is the main gene that affects the ovulation rate and litter size in sheep [35][36][37]. In addition, a series of studies have confirmed that the BMPR1B can affect follicular development, ovulation [38], and cause ovarian insufficiency [39].…”
Section: Discussionmentioning
confidence: 99%